2011
DOI: 10.1242/jcs.073171
|View full text |Cite
|
Sign up to set email alerts
|

ATP release due to Thy-1–integrin binding induces P2X7-mediated calcium entry required for focal adhesion formation

Abstract: SummaryThy-1, an abundant mammalian glycoprotein, interacts with avb3 integrin and syndecan-4 in astrocytes and thus triggers signaling events that involve RhoA and its effector p160ROCK, thereby increasing astrocyte adhesion to the extracellular matrix. The signaling cascade includes calcium-dependent activation of protein kinase Ca upstream of Rho; however, what causes the intracellular calcium transients required to promote adhesion remains unclear. Purinergic P2X7 receptors are important for astrocyte func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 41 publications
10
56
1
Order By: Relevance
“…28 These studies are supported by others demonstrating that P2X7-dependent Ca 2þ signaling is necessary for focal adhesion formation and migration in astrocytes. 22 On the basis of this evidence, we hypothesized that P2X7 activation and the subsequent change in P2X7 localization after injury promote rapid cytoskeletal rearrangements at the leading edge. Immunofluorescence studies demonstrated that focal adhesion proteins in cells that were scratch wounded in the presence or absence of oxATP were altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 These studies are supported by others demonstrating that P2X7-dependent Ca 2þ signaling is necessary for focal adhesion formation and migration in astrocytes. 22 On the basis of this evidence, we hypothesized that P2X7 activation and the subsequent change in P2X7 localization after injury promote rapid cytoskeletal rearrangements at the leading edge. Immunofluorescence studies demonstrated that focal adhesion proteins in cells that were scratch wounded in the presence or absence of oxATP were altered.…”
Section: Discussionmentioning
confidence: 99%
“…P2X7 signaling has been shown in lung epithelial cells to be upstream of focal adhesion formation. 22 We therefore analyzed whether inhibition of P2X7 in corneal epithelial cells altered focal adhesions after injury. Cultures were incubated in the presence or absence of oxATP, and scratchwounded cells were stained for talin or vinculin.…”
Section: P2x7 and Cell Migrationmentioning
confidence: 99%
“…We previously demonstrated that the P2X7R is required to increase Ca 2+ uptake and cell adhesion to the underlying matrix [20]. Here, we set out to study whether P2X7R is also required for Thy-1-stimulated migration of astrocytes.…”
Section: The P2x7 Receptor Is Required For Thy-1-induced Astrocyte Pomentioning
confidence: 97%
“…Strong astrocyte adhesion induced by Thy-1 also requires increased extracellular adenosine 5'-triphosphate (ATP), activation of the purinergic P2X7 receptor (P2X7R), and Ca 2+ entry into the cell [20]. Whether this molecular mechanism is also required for cell migration and how ATP is released from the cells to the extracellular media are questions that remain to be explored.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation